2022
DOI: 10.3390/cells11091574
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response and Differentiation of Bone Marrow-Derived Mesenchymal Stem/Stromal Cells in the Presence of Novel Multiple Myeloma Drug Melflufen

Abstract: Mesenchymal stem/stromal cells (MSCs) are self-renewing and multipotent progenitors, which constitute the main cellular compartment of the bone marrow stroma. Because MSCs have an important role in the pathogenesis of multiple myeloma, it is essential to know if novel drugs target MSCs. Melflufen is a novel anticancer peptide–drug conjugate compound for patients with relapsed refractory multiple myeloma. Here, we studied the cytotoxicity of melflufen, melphalan and doxorubicin in healthy human bone marrow-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Furthermore, it also reduces VEGF-induced migration of MM cells through transwell insert without affecting their viability, suggesting that cell homing and metastatization are halted [ 113 ]. Gebraad and collaborators [ 114 ] showed that BMSCs are sensitive to mel-flufen, abrogating their protective effect on MM cells and affecting BMSCs-mediated angiogenesis. Accordingly, mel-flufen inhibits angiogenesis of HUVEC co-cultured with BMSCs through the reduction of ECs sproutings and of α-SMA-positive pericytes [ 114 ] ( Figure 2 g).…”
Section: Anti-angiogenic Drugs In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it also reduces VEGF-induced migration of MM cells through transwell insert without affecting their viability, suggesting that cell homing and metastatization are halted [ 113 ]. Gebraad and collaborators [ 114 ] showed that BMSCs are sensitive to mel-flufen, abrogating their protective effect on MM cells and affecting BMSCs-mediated angiogenesis. Accordingly, mel-flufen inhibits angiogenesis of HUVEC co-cultured with BMSCs through the reduction of ECs sproutings and of α-SMA-positive pericytes [ 114 ] ( Figure 2 g).…”
Section: Anti-angiogenic Drugs In MMmentioning
confidence: 99%
“…Gebraad and collaborators [ 114 ] showed that BMSCs are sensitive to mel-flufen, abrogating their protective effect on MM cells and affecting BMSCs-mediated angiogenesis. Accordingly, mel-flufen inhibits angiogenesis of HUVEC co-cultured with BMSCs through the reduction of ECs sproutings and of α-SMA-positive pericytes [ 114 ] ( Figure 2 g). Mel-flufen, in combination with dexamethasone, significantly improved MM patients’ overall survival and was approved for relapsed/refractory patients resistant to proteasome inhibitors, IMiDs, and anti-CD38 mAbs (NCT02963493).…”
Section: Anti-angiogenic Drugs In MMmentioning
confidence: 99%